Pengaruh Jarak Tanam dan Jumlah Benih Perlubang Tanam Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea Mays Saacaratha L.) Bonanza F1 Di Desa Wairkoja, Kecamatan Kewapante, Kabupaten Sikka. - Yovita Yasintha Bolly (Agriculture Faculty of Flores University, 2018)
Plant Spacing and the Number of Seeds per Planting hole is one of the factors that affect plant growth and yield. therefore. the study entitled The Effect of Planting Distance and Number of Perforated Planting Seeds on Growth and Yield of Sweet Corn (Zea mays Saacaratha L.) Bonanza F1 in Wairkoja Village, Kewapante District, Sikka Regency, has been carried out. This study uses a randomized block design (RCBD), which consists of two (2) factors, namely, spacing (J) and the number of seeds per planting hole (W) as follows J1: Length 50 cm x Width 25 cm. These two factors are combined to obtain nine treatment combinations. The observed variables were plant height (cm), number of leaves (strands), wet weight of trees, N, P, K pH, and C-organic soil. Based on the research that has been done, it can be concluded that the treatment of spacing did not affect the growth and production of corn, the number of seeds did not affect the number of leaves and the combined treatment of the number of seeds and spacing did not affect the wet weight of the fruit.